A high flame retardant power cable and a method for manufacturing the same
Patent Information
- Application Number
- CN202611021513.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]现有电力电缆的阻燃改性技术仍存在明显不足:第一,阻燃方案多依赖高添加量的无机阻燃剂,如氢氧化铝、氢氧化镁,此类阻燃剂与有机基体相容性差,易发生团聚,不仅导致阻燃效率偏低,还会显著降低护套层力学性能,易出现脆化、开裂等问题;第二,护套层常用的PC/ABS与PC/PBT多为简单物理复配,塑料合金本身不具备本征阻燃性能,仅依靠外掺阻燃剂实现辅助阻燃,存在阻燃效率低、阻燃基团易迁移、长效稳定性差等缺陷;第三,护套层多为各组分物理共混体系,受热易软化、熔融滴落,火焰易沿滴落物扩散蔓延,且燃烧形成的炭层结构疏松、易破裂脱落,无法形成连续稳定的隔氧阻热屏障,难以实现持久高效阻燃
(1)本发明采用芥酸酰胺改性聚磷酸铵,芥酸酰胺分子通过酰胺基团与聚磷酸铵表面羟基(或氨基)的弱氢键/范德华力物理吸附,长链烷基向外伸展形成疏水保护层,降低聚磷酸铵颗粒表面能,提升与非极性基体的相容性和分散均匀性。本发明在保证阻燃效果的前提下,可显著降低阻燃剂添加量,同时提升阻燃效率。燃烧过程中,改性聚磷酸铵受热分解生成聚磷酸类脱水成炭剂,催化基体快速形成连续炭层,同时芥酸酰胺热解补充炭源,与聚磷酸铵协同提升成炭量与炭层致密度,增强隔氧、阻热、抑燃效果,使电力电缆氧指数显著提高、阻燃效率提升。此外,干法改性工艺无溶剂、无污染、操作简便,可直接利用现有高速混合设备完成,无需新增投资,工业化实用性强。
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to the field of power cable technology, and more particularly to a high flame-retardant power cable and its preparation method. Background Technology
[0002] As the core carrier of power transmission and distribution, the safety performance of power cables is directly related to the stable operation of industrial production and residential life. With the continuous expansion of application scenarios, more stringent requirements are placed on the flame retardant performance of cables. They not only need to have excellent flame retardancy and be difficult to ignite under open flame conditions, but also need to prevent molten dripping during combustion and thus avoid the spread of fire. At the same time, they should maintain good mechanical properties to meet the needs of cable installation, laying and long-term stable use.
[0003] Existing flame-retardant modification technologies for power cables still have significant shortcomings: First, most flame-retardant solutions rely on high amounts of inorganic flame retardants, such as aluminum hydroxide and magnesium hydroxide. These flame retardants have poor compatibility with organic matrices and are prone to agglomeration, resulting not only in low flame-retardant efficiency but also in significantly reducing the mechanical properties of the sheath layer, leading to problems such as embrittlement and cracking. Second, the commonly used PC / ABS and PC / PBT materials in the sheath layer are mostly simple physical blends. The plastic alloys themselves do not possess intrinsic flame-retardant properties and rely solely on external flame retardants for auxiliary flame retardancy, resulting in low flame-retardant efficiency, easy migration of flame-retardant groups, and poor long-term stability. Third, the sheath layer is mostly a physical blend system of various components, which is prone to softening and melting when heated. Flames can easily spread along the dripping material, and the char layer formed by combustion has a loose structure that is easy to break and fall off, failing to form a continuous and stable oxygen-barrier and heat-insulating barrier, making it difficult to achieve long-lasting and efficient flame retardancy.
[0004] Therefore, developing a power cable that combines high flame retardancy, excellent mechanical properties, and simple manufacturing process suitable for industrial production has become an urgent technical problem to be solved in this field. Summary of the Invention
[0005] To address the aforementioned problems in the existing technology, this invention provides a high flame-retardant power cable and its preparation method. Through the synergistic effect of modified ammonium polyphosphate, grafted modified plastic alloy, and lightweight co-crosslinked network, the flame-retardant performance and mechanical properties are simultaneously improved while reducing the amount of flame retardant added. Moreover, the preparation process is simple and easy to industrialize.
[0006] The objective of this invention can be achieved through the following technical solutions: In a first aspect, a high flame-retardant power cable is provided, comprising a conductor, an insulation layer, and a sheath layer arranged sequentially from the inside out. The sheath layer comprises, by weight, 50-60 parts of polyethylene, 60-70 parts of ethylene-vinyl acetate copolymer, 10-15 parts of methyl vinyl silicone rubber, 30-40 parts of modified ammonium polyphosphate, 0.5-1 part of dicumyl peroxide, 8-10 parts of graft-modified plastic alloy, and 1-1.5 parts of antioxidant. The modified ammonium polyphosphate was prepared by modifying erucamide.
[0007] In this process, dicumyl peroxide acts as a crosslinking agent, initiating the generation of free radicals in the molecular chains of polyethylene, ethylene-vinyl acetate copolymer, and methyl vinyl silicone rubber, and causing co-crosslinking to form a lightweight co-crosslinked network.
[0008] Furthermore, the modified ammonium polyphosphate is prepared by mixing ammonium polyphosphate and erucamide at a mass ratio of 100:2~4 and then dry-stirring at high speed.
[0009] Furthermore, the ammonium polyphosphate is of type APP-II with a degree of polymerization of 1000~1500; the process conditions for the dry high-speed stirring are: stirring speed of 800~1200 r / min, stirring temperature of 60~80℃, and stirring time of 20~30 min.
[0010] Furthermore, the grafted modified plastic alloy is a compound of phosphorus-based grafted PC / ABS and nitrogen-based grafted PC / PBT; the phosphorus-based grafted PC / ABS is obtained by melt grafting PC / ABS with non-halogenated phosphorus-based grafting monomers, and the nitrogen-based grafted PC / PBT is obtained by melt grafting PC / PBT with nitrogen-based grafting monomers.
[0011] Furthermore, the PC / ABS is model CE3210, and the mass ratio of PC / ABS to non-halogenated phosphorus graft monomer is 100:2~4; the PC / PBT is model V3900WX, and the mass ratio of PC / PBT to nitrogen-based graft monomer is 100:2~4.
[0012] Furthermore, the non-halogenated phosphorus graft monomer is an organophosphate containing an allyl double bond, preferably a triallyl phosphate; the nitrogen-based graft monomer is a nitrogen-containing flame-retardant monomer containing an amide double bond, preferably methacrylamide; the melt grafting temperature is 180~200℃, and the process is completed using a twin-screw extruder.
[0013] Furthermore, the mass ratio of the phosphorus-grafted PC / ABS to the nitrogen-grafted PC / PBT is 1:2~3.
[0014] Further, the antioxidant is one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(2,4-di-tert-butylphenyl)phosphite, and dithioethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; the conductor is a copper conductor, and the insulating layer is a cross-linked polyethylene insulating layer.
[0015] Secondly, a method for preparing a highly flame-retardant power cable is provided, comprising the following steps: S1. Extruding a cross-linked polyethylene insulation layer onto the outside of a copper conductor and cooling it yields a semi-finished cable. S2. Prepare modified ammonium polyphosphate and grafted modified plastic alloy separately for later use; wherein, the preparation of grafted modified plastic alloy includes compounding phosphorus-based grafted PC / ABS and nitrogen-based grafted PC / PBT at a mass ratio of 1:2~3. S3. Polyethylene, ethylene-vinyl acetate copolymer, methyl vinyl silicone rubber, modified ammonium polyphosphate, dicumyl peroxide, grafted modified plastic alloy and antioxidant are added to a high-speed mixer and mixed to obtain the sheath layer mixture. S4. Extrude the sheath layer mixture onto the outside of the cable semi-finished product, and after cross-linking treatment and cooling, a high flame-retardant power cable is obtained.
[0016] Furthermore, in step S3, the stirring speed of the high-speed mixer is 800~1200 r / min, and the mixing time is 20~30 min; in step S4, the extrusion temperature is 160~180℃, the crosslinking temperature is 170℃, and the crosslinking time is 10~15 min.
[0017] The beneficial effects of this invention are as follows: (1) This invention uses erucamide to modify ammonium polyphosphate. Erucamide molecules are physically adsorbed by weak hydrogen bonds / van der Waals forces between the amide groups and the hydroxyl (or amino) groups on the surface of ammonium polyphosphate. The long-chain alkyl groups extend outward to form a hydrophobic protective layer, reducing the surface energy of the ammonium polyphosphate particles and improving compatibility and dispersion uniformity with the non-polar matrix. This invention can significantly reduce the amount of flame retardant added while improving the flame retardant efficiency, while ensuring the flame retardant effect. During combustion, the modified ammonium polyphosphate is thermally decomposed to generate polyphosphate dehydrating char-forming agents, which catalyze the rapid formation of a continuous char layer on the matrix. At the same time, the pyrolysis of erucamide replenishes the char source, and together with the ammonium polyphosphate, it synergistically increases the amount of char and the density of the char layer, enhancing the oxygen barrier, heat barrier, and flame suppression effects, thus significantly improving the oxygen index and flame retardant efficiency of the power cable. In addition, the dry modification process is solvent-free, pollution-free, and easy to operate. It can be directly completed using existing high-speed mixing equipment without additional investment, making it highly practical for industrial application.
[0018] (2) This invention utilizes melt grafting technology to chemically graft non-halogenated phosphorus-based flame-retardant monomers and nitrogen-based flame-retardant monomers onto the molecular chains of PC / ABS and PC / PBT, respectively, thereby endowing the plastic alloys with intrinsic flame-retardant properties. During combustion, the phosphorus-based grafted components promote dehydration and char formation in the matrix, creating a dense solid-phase char layer. The nitrogen-based grafted components release inert gases such as ammonia and nitrogen upon heating, diluting the concentration of combustible gases and achieving gas-phase flame retardancy. The combination of phosphorus-based grafted PC / ABS and nitrogen-based grafted PC / PBT forms a highly efficient phosphorus-nitrogen synergistic system, which further enhances the three-phase synergistic flame-retardant effect with modified ammonium polyphosphate, significantly improving char integrity and flame-retardant stability, enabling the vertical combustion rating of the power cable to reach V. Grade 0, no molten dripping. Simultaneously, grafting modification enhances the interfacial bonding between the plastic alloy and the matrix, improves the overall mechanical properties of the sheath layer, and significantly increases tensile strength.
[0019] (3) In this invention, dicumyl peroxide is used as a crosslinking agent to initiate the crosslinking of polyethylene and ethylene at the crosslinking temperature. Vinyl acetate copolymer and methyl vinyl silicone rubber molecular chains form a mild chemical co-crosslink, which, together with grafted modified plastic alloy, constructs a lightweight co-crosslinked network. This network improves the thermal stability and high-temperature structural strength of the matrix, inhibiting softening and molten dripping upon heating. Simultaneously, as a rigid physical framework, it supports and fixes the composite carbon layer formed by modified ammonium polyphosphate and grafted modified plastic alloy, preventing the carbon layer from cracking, detaching, or pulverizing, ensuring long-term effective oxygen barrier and heat insulation, and significantly improving flame retardancy and reliability. The crosslinked structure also enhances the mechanical strength and aging resistance of the matrix, increasing the retention rate of tensile strength after cable thermal aging, resulting in greater long-term stability. Detailed Implementation
[0020] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.
[0021] Preparation Example 1: Preparation of Modified Ammonium Polyphosphate Ammonium polyphosphate and erucamide were added to a high-speed mixer at a mass ratio of 100:3. The mixing speed was 1000 r / min, the mixing temperature was 70℃, and the mixing time was 25 min. After cooling to room temperature, the modified ammonium polyphosphate was obtained (corresponding to Example 1).
[0022] Following the above process, the mass ratio of ammonium polyphosphate to erucamide was adjusted to 100:2, the stirring speed was 800 r / min, the stirring temperature was 60℃, and the stirring time was 30 min, to obtain the modified ammonium polyphosphate corresponding to Example 2.
[0023] Following the above process, the mass ratio of ammonium polyphosphate to erucamide was adjusted to 100:4, the stirring speed was 1200 r / min, the stirring temperature was 80℃, and the stirring time was 20 min, to obtain the modified ammonium polyphosphate corresponding to Example 3.
[0024] Preparation Example 2: Preparation of Graft-Modified Plastic Alloy Phosphorus-grafted PC / ABS: CE3210 type PC / ABS and triallyl phosphate were added to a twin-screw extruder at a mass ratio of 100:3, melt-grafted at 190°C, and granulated to obtain phosphorus-grafted PC / ABS (corresponding to Example 1). The mass ratio was adjusted to 100:2, and the grafting was carried out at 180°C to obtain the phosphorus-based grafted PC / ABS corresponding to Example 2.
[0025] The mass ratio was adjusted to 100:4, and the grafting was carried out at 200°C to obtain the phosphorus-based grafted PC / ABS corresponding to Example 3.
[0026] Nitrogen-grafted PC / PBT: V3900WX type PC / PBT and methacrylamide were added to a twin-screw extruder at a mass ratio of 100:3, melt-grafted at 190°C, and granulated to obtain nitrogen-grafted PC / PBT (corresponding to Example 1). By adjusting the mass ratio to 100:2 and performing melt grafting at 180°C, nitrogen-grafted PC / PBT corresponding to Example 2 was obtained.
[0027] The mass ratio was adjusted to 100:4, and the nitrogen-grafted PC / PBT corresponding to Example 3 was obtained by melt grafting at 200°C.
[0028] Compounding: The above phosphorus-based grafted PC / ABS and nitrogen-based grafted PC / PBT were compounded at a mass ratio of 1:2.5 (corresponding to Example 1), and compounded at 1:2 and 1:3 respectively to prepare grafted modified plastic alloys corresponding to Examples 2 and 3.
[0029] Example 1 1. Formula (parts by weight) The sheath layer comprises, by weight: 55 parts polyethylene, 65 parts ethylene-vinyl acetate copolymer, 13 parts methyl vinyl silicone rubber, 35 parts modified ammonium polyphosphate, 0.8 parts dicumyl peroxide, 9 parts grafted modified plastic alloy, and 1.2 parts pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. The conductor is a copper conductor, and the insulation layer is a cross-linked polyethylene insulation layer.
[0030] 2. Preparation method S1. Extruding a cross-linked polyethylene insulation layer onto the outside of a copper conductor and cooling it yields a semi-finished cable. S2. Prepare modified ammonium polyphosphate and grafted modified plastic alloy according to preparation examples 1 and 2, and set aside for later use; S3. Polyethylene, ethylene-vinyl acetate copolymer, methyl vinyl silicone rubber, modified ammonium polyphosphate, dicumyl peroxide, graft-modified plastic alloy and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] are added to a high-speed mixer and stirred at 1000 r / min for 25 min to obtain the sheath layer mixture. S4. Extrude the sheath layer mixture onto the outside of the cable semi-finished product at 170℃, crosslink at 170℃ for 12 minutes, and cool to obtain a high flame retardant power cable.
[0031] Example 2 1. Formula (parts by weight) The sheath layer comprises, by weight: 50 parts polyethylene, 60 parts ethylene-vinyl acetate copolymer, 10 parts methyl vinyl silicone rubber, 30 parts modified ammonium polyphosphate, 0.5 parts dicumyl peroxide, 8 parts graft-modified plastic alloy, and 1 part tris(2,4-di-tert-butylphenyl) phosphite. The conductor is a copper conductor, and the insulation layer is a cross-linked polyethylene insulation layer.
[0032] 2. Preparation method S1. Extruding a cross-linked polyethylene insulation layer onto the outside of a copper conductor and cooling it yields a semi-finished cable. S2. Prepare modified ammonium polyphosphate and grafted modified plastic alloy according to preparation examples 1 and 2, and set aside for later use; S3. Polyethylene, ethylene-vinyl acetate copolymer, methyl vinyl silicone rubber, modified ammonium polyphosphate, dicumyl peroxide, grafted modified plastic alloy and tris(2,4-di-tert-butylphenyl) phosphite are added to a high-speed mixer and stirred at 800 r / min for 30 min to obtain the sheath layer mixture. S4. Extrude the sheath layer mixture onto the outside of the cable semi-finished product at 160℃, crosslink at 170℃ for 15 minutes, and cool to obtain a high flame retardant power cable.
[0033] Example 3 1. Formula (parts by weight) The sheath layer comprises, by weight: 60 parts polyethylene, 70 parts ethylene-vinyl acetate copolymer, 15 parts methyl vinyl silicone rubber, 40 parts modified ammonium polyphosphate, 1 part dicumyl peroxide, 10 parts graft-modified plastic alloy, and 1.5 parts pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. The conductor is a copper conductor, and the insulation layer is a cross-linked polyethylene insulation layer.
[0034] 2. Preparation method S1. Extruding a cross-linked polyethylene insulation layer onto the outside of a copper conductor and cooling it yields a semi-finished cable. S2. Prepare modified ammonium polyphosphate and grafted modified plastic alloy according to preparation examples 1 and 2, and set aside for later use; S3. Polyethylene, ethylene-vinyl acetate copolymer, methyl vinyl silicone rubber, modified ammonium polyphosphate, dicumyl peroxide, grafted modified plastic alloy and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] are added to a high-speed mixer and stirred at 1200 r / min for 20 min to obtain the sheath layer mixture. S4. Extrude the sheath layer mixture onto the outside of the cable semi-finished product at 180°C, crosslink at 170°C for 10 minutes, and cool to obtain a high flame-retardant power cable.
[0035] Comparative Example 1 Based on Example 1, the modified ammonium polyphosphate was replaced with unmodified ammonium polyphosphate, and other conditions were the same as in Example 1.
[0036] Comparative Example 2 Based on Example 1, the grafted modified plastic alloy was replaced with an ungrafted modified plastic alloy, while other conditions remained the same as in Example 1.
[0037] Comparative Example 3 Based on Example 1, without the addition of dicumyl peroxide, all other conditions were the same as in Example 1.
[0038] Comparative Example 4 Based on Example 1, unmodified ammonium polyphosphate, ungrafted modified plastic alloy, and no dicumyl peroxide were used, while other conditions were the same as in Example 1.
[0039] Comparative Example 5 Cable materials were prepared according to the formula and preparation method in CN108586908A.
[0040] Performance testing The power cables prepared in Examples 1-3 and Comparative Examples 1-5 were tested according to the following standards, and the results are shown in Tables 1 and 2: Oxygen index was tested according to GB / T 2406.2-2009; vertical burning rating and melt dripping were tested according to GB / T 2408-2021; tensile strength was tested according to GB / T 2951.11-2008; and tensile strength retention rate after heat aging was tested according to GB / T 2951.12-2008.
[0041] Table 1 Performance test results of the embodiments
[0042] Table 2 Comparative Performance Test Results
[0043] The results showed that Examples 1-3 achieved a comprehensive effect of high flame retardancy, no dripping, excellent mechanical properties, and strong thermal stability through the synergistic effect of modified ammonium polyphosphate, grafted modified plastic alloy, and lightweight cross-linked network, meeting the requirements for high flame retardant power cables. Compared with the examples, the performance of each comparative example was significantly reduced due to the lack of corresponding invention points: Comparative Example 1 did not modify the ammonium polyphosphate, resulting in poor compatibility between the flame retardant and the matrix, easy agglomeration, insufficient char formation, and reduced flame retardant efficiency, with an oxygen index of only 37.2% and a vertical burning rating of only V-1. At the same time, agglomeration destroyed the continuity of the matrix, and the tensile strength was significantly reduced. Comparative Example 2 did not use grafted modified plastic alloy, and the plastic alloy had no intrinsic flame retardancy and no phosphorus-nitrogen synergy. Relying solely on ammonium polyphosphate for flame retardancy, the flame retardant effect was significantly weakened, with an oxygen index of 38.5%, a vertical burning rating of V-1, and reduced compatibility with the matrix, resulting in slightly lower mechanical properties. Comparative Example 3, lacking dicumyl peroxide and light cross-linking, had no cross-linked matrix, resulting in easy softening and significant melting and dripping upon heating. The char layer formed during combustion lacked skeletal support, making it prone to cracking and detachment, leading to a decrease in flame retardancy persistence. Its oxygen index was 39.3%, achieving a vertical burning V-1 rating. Furthermore, the absence of network reinforcement significantly reduced its thermal aging stability. Comparative Example 4, due to flame retardant agglomeration, lack of intrinsic flame retardancy, and absence of cross-linking support, failed to meet all standards for flame retardancy, mechanical properties, and thermal stability. Its oxygen index was only 35.8%, and it exhibited severe dripping during combustion, completely failing to meet high flame retardancy requirements. Comparative Example 5, referencing the technical solution of CN108586908A, had a flame retardant addition amount as high as 150-190 parts, but its oxygen index was only about 31.4%, failing to reach the UL94 V-0 rating.
[0044] In summary, this invention addresses the issues of flame retardant agglomeration and insufficient char formation by modifying ammonium polyphosphate, achieves intrinsic flame retardancy and synergistic effects of phosphorus and nitrogen by grafting modified plastic alloys, and solves the problems of melt dripping and easy char layer breakage by lightweight cross-linking network. All three are indispensable and work together to achieve a high flame retardant power cable with high flame retardancy, no dripping, excellent mechanical properties, and strong thermal stability.
[0045] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A high flame-retardant power cable, comprising a conductor, an insulation layer, and a sheath layer arranged sequentially from the inside out, characterized in that, The sheath layer comprises, by weight: 50-60 parts polyethylene, 60-70 parts ethylene-vinyl acetate copolymer, 10-15 parts methyl vinyl silicone rubber, 30-40 parts modified ammonium polyphosphate, 0.5-1 part dicumyl peroxide, 8-10 parts grafted modified plastic alloy, and 1-1.5 parts antioxidant. The modified ammonium polyphosphate was prepared by modifying erucamide.
2. The high flame-retardant power cable according to claim 1, characterized in that, The modified ammonium polyphosphate is prepared by mixing ammonium polyphosphate and erucamide at a mass ratio of 100:2~4 and then dry-stirring at high speed.
3. The high flame-retardant power cable according to claim 2, characterized in that, The ammonium polyphosphate is of type APP-II with a degree of polymerization of 1000~1500; the dry high-speed stirring process conditions are: stirring speed 800~1200 r / min, stirring temperature 60~80℃, and stirring time 20~30 min.
4. The high flame-retardant power cable according to claim 1, characterized in that, The grafted modified plastic alloy is a compound of phosphorus-based grafted PC / ABS and nitrogen-based grafted PC / PBT; the phosphorus-based grafted PC / ABS is obtained by melt grafting PC / ABS with non-halogenated phosphorus-based grafting monomers, and the nitrogen-based grafted PC / PBT is obtained by melt grafting PC / PBT with nitrogen-based grafting monomers.
5. The high flame-retardant power cable according to claim 4, characterized in that, The PC / ABS is model CE3210, and the mass ratio of PC / ABS to non-halogenated phosphorus graft monomer is 100:2~4; the PC / PBT is model V3900WX, and the mass ratio of PC / PBT to nitrogen-based graft monomer is 100:2~4.
6. The high flame-retardant power cable according to claim 4, characterized in that, The non-halogenated phosphorus graft monomer is an organophosphate containing an allyl double bond, preferably a triallyl phosphate; the nitrogen-based graft monomer is a nitrogen-containing flame-retardant monomer containing an amide double bond, preferably methacrylamide; the melt grafting temperature is 180~200℃, and the process is completed using a twin-screw extruder.
7. The high flame-retardant power cable according to claim 1, characterized in that, The mass ratio of phosphorus-grafted PC / ABS to nitrogen-grafted PC / PBT is 1:2~3.
8. The high flame-retardant power cable according to claim 1, characterized in that, The antioxidant is one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(2,4-di-tert-butylphenyl)phosphite, and dithioethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; the conductor is a copper conductor, and the insulation layer is a cross-linked polyethylene insulation layer.
9. A method for preparing a high flame-retardant power cable as described in any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Extruding a cross-linked polyethylene insulation layer onto the outside of a copper conductor and cooling it yields a semi-finished cable. S2. Prepare modified ammonium polyphosphate and grafted modified plastic alloy separately for later use; wherein, the preparation of grafted modified plastic alloy includes compounding phosphorus-based grafted PC / ABS and nitrogen-based grafted PC / PBT at a mass ratio of 1:2~3. S3. Polyethylene, ethylene-vinyl acetate copolymer, methyl vinyl silicone rubber, modified ammonium polyphosphate, dicumyl peroxide, grafted modified plastic alloy and antioxidant are added to a high-speed mixer and mixed to obtain the sheath layer mixture. S4. Extrude the sheath layer mixture onto the outside of the cable semi-finished product, and after cross-linking treatment and cooling, a high flame-retardant power cable is obtained.
10. The method for preparing a high flame-retardant power cable according to claim 9, characterized in that, In step S3, the stirring speed of the high-speed mixer is 800~1200 r / min, and the mixing time is 20~30 min; in step S4, the extrusion temperature is 160~180℃, the crosslinking temperature is 170℃, and the crosslinking time is 10~15 min.
Citation Information
Patent Citations
125 DEG C radiation-crosslinked, halogen-free, low-smoke, flame-retardant oil-resistant and cold-resistant cable material and preparation method thereof
CN108586908A